Phosphahelicenes: From Chiroptical and Photophysical Properties to OLED Applications. Issue 20 (12th March 2019) - Yavari, Keihann; Delaunay, Wylliam; De Rycke, Nicolas; Reynaldo, Thibault; Aillard, Paul; Srebro‐Hooper, Monika; Chang, Victoria Y.; Muller, Gilles; Tondelier, Denis; Geffroy, Bernard; Voituriez, Arnaud; Marinetti, Angela; et al.
Abstract: Herein, the experimental physicochemical and chiroptical properties of a series of phosphahelicenes are reported, focusing on their UV/Vis absorption, luminescence, electronic circular dichroism, optical rotations, and circularly polarized luminescence. Furthermore, detailed analysis of absorption and ECD spectra performed with the help of quantum‐chemical calculations allowed us to highlight general features of these helicenic phosphines. Finally, due to well‐suited electrochemical properties and thermal stability, the systems were successfully used as emitters in organic light‐emitting diodes. Abstract : Spirals of light : The experimental physicochemical and chiroptical properties of a series of phosphahelicenes are reported along with their theoretical analysis, focusing on their UV/Vis absorption, luminescence, electronic circular dichroism (ECD), optical rotations, and circularly polarized luminescence. Due to well‐suited electrochemical properties and thermal stability, the systems were successfully used as emitters in organic light‐emitting diodes.